Formulation and In vitro Characterization of Hydrochlorothiazide Gastroretentive Floating Drug Delivery System - Hasan, Md Asif; Sultana, Sabiha; Sultana, Sabiha; Bhuiyan, Md Masud Kaisar; Reza, Md Selim; Hossain, Mohammad Salim (Dhaka University Journal of Pharmaceutical Sciences, 2016)
The purpose of the study was to develop and optimize floating bioadhesive gastroretentive drug delivery system (GRDDS) exhibiting a unique combination of floatation and bioadhesion to prolong residence in the stomach, using hydrochlorothiazide (HCTZ) as a model drug. Formulated matrix tablets were prepared by direct compression method with two different rate controlling polymer HPMC K4M and Carbopol 971. The formulated tablets were evaluated for physical characterization, floating lag time, swelling index and drug content uniformity. The drug release study was carried out in 0.1N HCl as the medium (pH 1.2) for 8 hours using USP type II dissolution apparatus and investigated the effects of polymers on the drug release profile. In vitro buoyancy study results found to be 1033 sec and >8 h, floating lag time and total floating time respectively. Simulated drug release pattern in different kinetic models of Korsmeyer-Peppas release suggests that the mechanism controlling of the drug release from all formulations was the anomalous non-Fickian or anomalous release. Polymer with lower viscosity (HMPC K4M) was found to be beneficial than higher viscosity polymer (Carbopol 971) in improving the release properties of gastric floating drug delivery system. Incorporation of Carbopol in formulation also helped in maintaining buoyancy of system with desirable drug release. Further study is necessary in case of in vitro- in vivo relationship, but this study will ready to lend a hand to future scientists working in this field to successfully exploit the potential of this drug delivery system for the advantage of mankind. Dhaka Univ. J. Pharm. Sci. 14(2): 163-170, 2015 (December)